COMPOSITIONAL AND TECHNOLOGICAL FOUNDATIONS FOR UTILIZING NATIONAL MINIATURE ELEMENTS IN MODERN GARMENT DECORATION - Mokhinur Rakhimdjonova; Malika Usmanova; Mokhinur Berdimurodova; Risolat Kuchkarova; Saodat Pardayeva (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  explores  the  compositional  and  technological  foundations  of incorporating national miniature elements into the decoration of modern garments. The relevance  of  this  research  lies  in  the  significant  decline  of  interest  in  handcrafted miniature  art  due  to  the  rapid  advancement  of  contemporary  technologies. Consequently, preserving national heritage and harmonizing it with modern design has become  a  crucial  task.  The  paper  analyzes  the  artistic-compositional  principles  of integrating miniature elements into clothing design, alongside the technical aspects of their  application.  Furthermore,  the  study  examines  the  development  of  garment samples tailored for the image of the modern business woman based on these elements. The findings of this research contribute to the creation of innovative design solutions by blending traditional national artistic traditions with contemporary fashion.